International Migration and Nutritional Outcomes in Tajikistan - Azzarri, Carlo; Zezza, Alberto (2012)
Tajikistan is the country with the largest share of remittances to GDP in the world. At the same time it suffers from stubbornly high levels of child malnutrition against which only very slow progress has been made. This paper investigates the relationship between international migration and child malnutrition, using data from a recent nationally representative household survey. There are theoretical reasons to expect that migration may be exerting both positive and negative effects on nutrition and food security, so that understanding what the net effect may be is essentially an empirical question. Our results indicate that migration appears to be playing a positive role in enhancing child growth patterns (as measured by height-for-age z-scores) in the country. We explore some of the possible channels through which this effect might be operating and find that one such channel is by increasing households' kilocalorie consumption.